Daily intake of Kaempferia parviflora extract decreases abdominal fat in overweight and preobese subjects: a randomized, double-blind, placebo-controlled clinical study - Yoshino, Susumu; Awa, Riyo; Miyake, Yasuo; Fukuhara, Ikuo; Sato, Hisao; Ashino, Toyotada; Tomita, Shinpei; Kuwahara, Hitoshige (Diabetes, metabolic syndrome and obesity, 2018)
Obesity is a serious problem, which is now a worldwide health problem. extract (KPE) exhibits anti-obesity effects in animals. However, as no clinical trials have evaluated the anti-obesity effects of KPE in humans, we examined the effects of KPE in reducing abdominal fat in overweight and preobese Japanese subjects. A 12-week, single-center, randomized, double-blind, placebo-controlled clinical trial was conducted. Seventy-six subjects (males and females aged 20 to <65 years) with a body mass index ≥24 and <30 kg/m were randomly assigned into two groups. The subjects in each group ingested one capsule of placebo or active KPE (containing 150 mg of KPE) once daily for 12 weeks. The primary outcome was reduction in visceral fat area as determined by computed tomography scanning. The key secondary outcomes were reductions in subcutaneous fat area and total fat area. Subgroup analysis was also performed in healthy subjects without dyslipidemia, hypertension, or hyperglycemia. The safety of KPE ingestion was also evaluated. Compared with the placebo group, the active KPE group exhibited significant reduction in abdominal fat area (visceral, subcutaneous, and total fat) and triglyceride levels after 12 weeks. Subgroup analyses demonstrated a significant reduction in abdominal fat area and triglyceride levels in healthy subjects compared with the placebo group after 12 weeks. Neither group exhibited adverse events related to the test foods or clinically relevant abnormal changes in physical, biochemical, or hematologic parameters, or in urinalysis results and medical interview. Daily ingestion of KPE safely reduces body fat, particularly abdominal fat, in Japanese overweight and preobese subjects.